PENGARUH PEMBELAJARAN BERBASIS MOVING CLASS TERHADAP PRESTASI HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI DI SMA NEGERI 01 MALANG - Septiara Septiara; Anwar Sa’dullah; Abdul Jalil (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This study aims to find out how the influence of moving class learning on student learning outcomes on PAI subjects in SMA 01 Malang. The problem that often occurs is the feeling bored in following the learning process. Students become unenthusiastic and passionate in learning, the atmosphere becomes rigid and monotonous. With the application of moving class learning systems, it is expected to change the way students learn from passive learning to be active, so that it impacts on increased learning outcomes. This research is a type of quantitative research using questionnaires, interviews, observation and documentation. Data collection techniques used were questionnaires methodes, observations methodes and interviews methodes to obtain data about the implementation of moving class learning (X) and documentation to obtain data on student achievement (Y). The research data that has been collected was analyzed using one predictor regression analysis technique. The results of this study indicate that there is a positive influence from the implementation of moving class based learning on student achievement on PAI subjects in public high school 01 Malang.